A Geo-Statistical Analysis of Road Mortality in the Enlarged EU - Isabelle Thomas; Vojtech Eksler; Sylvain Lassarre (European Regional Science Association (ERSA), 2006)
This paper aims at showing and understanding the spatial regional disparities hidden behind average national statistics on road fatalities in Europe; special attention is given on the EU last enlargement. The work is not limited on differences descriptions, but unveils what is hidden behind the observed infra-national heterogeneity in terms of road risk. It is indeed common practice to compare countries in terms of road safety performance and to rank them in terms of a risk indicator such as the mortality rate, which is often expressed by the number of fatalities due to road accidents per 100,000 inhabitants. Some countries are known for their very bad risk records and are often pointed out by national or international authorities, without any understanding of the regional differences hidden behind a national mean value. The data analysis shows that changes in the level of spatial aggregation of the data produce significant differences in the variables describing the level of road safety, and hence in operational recommendation and conclusions. Beside the differences in national conditions and polices, the regional differences in road environment characteristics, traffic performance, road user mix, travel speeds, seat-belt use, and availability of emergency care have been major contributors to these variations. Road safety professionals and decision makers should be aware of the differences existing when trying to reduce road toll of the country in sustainable and cost-effective way.
Keywords: 330